2011
DOI: 10.1097/spv.0b013e318239b57d
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nerve Evaluation in Women

Abstract: : Our cohort demonstrates that those patients who had an equivocal or failed outcome of office-based PNE were more likely to have a neurological insult. Patients with neurological insult who are considered appropriate candidates for neuromodulation trial should undergo staged implantation with quadruple tined lead in the operating room to provide these patients with the greatest opportunity for successful outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Of the 24 PNE nonresponders, 8 patients (33.3%) had either Parkinson's disease or unspecified dementia. These findings are supported by Crites‐Bachert et al, 18 who previously demonstrated that patients with an equivocal or failed PNE outcome were more likely to have a neurological insult, and Amundsen et al 20 who suggested that neurologic conditions may be associated with decreased cure rates. Patients with neurologic bladder disorders appear to benefit from a two‐staged SNM approach, as Wallace et al noted that 28 of 33 neurogenic patients (85%) proceeded to permanent implant following successful tined lead screening, including 4 of 6 patients (67%) with Parkinson's disease 21 .…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Of the 24 PNE nonresponders, 8 patients (33.3%) had either Parkinson's disease or unspecified dementia. These findings are supported by Crites‐Bachert et al, 18 who previously demonstrated that patients with an equivocal or failed PNE outcome were more likely to have a neurological insult, and Amundsen et al 20 who suggested that neurologic conditions may be associated with decreased cure rates. Patients with neurologic bladder disorders appear to benefit from a two‐staged SNM approach, as Wallace et al noted that 28 of 33 neurogenic patients (85%) proceeded to permanent implant following successful tined lead screening, including 4 of 6 patients (67%) with Parkinson's disease 21 .…”
Section: Discussionmentioning
confidence: 56%
“…The current study is limited by its retrospective design. Due to the small cohort with neurologic conditions, our results highlighting this comorbidity as predictive of PNE failure may be subject to type 1 statistical error; however, previous studies with comparable sample sizes have supported this claim 18,20 . Ultimately, larger studies investigating this patient population are necessary to fully confirm these findings.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations